2011
DOI: 10.1136/ard.2011.152074
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 22 serum levels are associated with radiographic progression in rheumatoid arthritis

Abstract: ObjectivesTo study the role of interleukin 22 in rheumatoid arthritis (RA). Methods IL-22 serum levels were measured in patients with early, treatment-naive RA (n=49) and in 45 age-and sex-matched healthy individuals as controls. Patients were assessed clinically and radiographically at baseline and followed up for 2 years. Correlations of IL-22 serum levels were sought with parameters of disease activity, serological markers, demographic factors and the incidence of erosions. IL-22 production by peripheral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
60
1
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 24 publications
10
60
1
9
Order By: Relevance
“…In our study, we observed significantly elevated levels of IL-22 in serum of RA patients compared to healthy controls (p=.022). Our data are in accordance with previous reports that found elevation of IL-22 in serum and plasma of patients with RA [34][35][36][37] . In consistent with our T cells were correlated positively with the disease activity in RA patients and the percentage of these cells were correlated positively with the levels of plasma IL-22 in these patients 36 .…”
Section: Resultssupporting
confidence: 83%
“…In our study, we observed significantly elevated levels of IL-22 in serum of RA patients compared to healthy controls (p=.022). Our data are in accordance with previous reports that found elevation of IL-22 in serum and plasma of patients with RA [34][35][36][37] . In consistent with our T cells were correlated positively with the disease activity in RA patients and the percentage of these cells were correlated positively with the levels of plasma IL-22 in these patients 36 .…”
Section: Resultssupporting
confidence: 83%
“…This is consistent with a recent report that links IL-22 serum concentrations with radiographic progression in RA. 41 In summary, our results suggest that the IL-23R Arg381Gln substitution may alter IL-23R function, thereby influencing serum IL-17A concentrations. In comparison, polymorphisms in the IL-12 Figure 2.…”
Section: à5mentioning
confidence: 93%
“…Other studies have indicated the similar relationship between IL-22 and RA, where serum IL-22 levels were found to be increased in patients with RA compared with controls 2,3,4,5 , and high IL-22 levels correlated with bone erosions 4 . The IL-22 concentration in synovial fluid was higher in patients with RA compared with controls 2,3 .…”
Section: To the Editormentioning
confidence: 62%
“…The IL-22 concentration in synovial fluid was higher in patients with RA compared with controls 2,3 . In patients with RA, Th17 cells were recognized to produce higher IL-22 4 . Th22 cells also produced IL-22 and the expression of Th22 cells.…”
Section: To the Editormentioning
confidence: 99%